KINERJA DEWAN PERWAKILAN RAKYAT (DPRD) PEREMPUAN DI KABUPATEN SUMBAWA PERIODE 2019-2024 - Leni Nurul Kariyani (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to analyze the performance of female members of the Regional House of Representatives (DPRD) in Sumbawa Regency during the 2019–2024 period through three main indicators: accountability, responsiveness, and effectiveness, as well as to identify the internal and external factors that influence their performance. This research employs a qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The results show that accountability is reflected through transparent activity reporting and public openness. Responsiveness is demonstrated by their attention to public aspirations, particularly from vulnerable groups such as women, WRSE, and low-income communities. The effectiveness of legislative and oversight duties is relatively good, although they still face structural barriers and patriarchal cultural norms. Internal factors that influence their performance include motivation, capability, personality, and health conditions. Meanwhile, external factors encompass organizational culture, compensation systems, the use of technology, and support for training and development. This study concludes that the presence of women in the DPRD has made a real contribution to local political processes, although strengthening their substantive representation remains necessary to ensure their roles are not merely symbolic.